Improving Passport Access for Vulnerable Groups: A User Acceptance Analysis of the SIAP RAMAH Application - Gunawan Ari Nursanto; Rasona Sunara Akbar; Budy Mulyawan; Arief Febrianto (Jurnal Ilmiah Kebijakan Hukum, 2025)
This study explores the implementation of the SIAP RAMAH (Sistem Aplikasi Paspor Ramah HAM) application, a human rights-based passport service management system developed by the Blitar Immigration Office in Indonesia. The objective was to assess user acceptance of this digital innovation using the Technology Acceptance Model (TAM), focusing specifically on vulnerable groups, including elderly individuals, persons with disabilities, infants, and pregnant women. The methodology employed a qualitative descriptive approach through participant observations and structured interviews with purposely selected system administrators, operators, and users. Findings revealed that SIAP RAMAH was generally well-received by vulnerable users due to its intuitive interface, reduced processing times, and streamlined application procedures. The study identified a strong relationship between TAM constructs-Perceived Usefulness and Perceived Ease of Use-and system adoption, with ease of use emerging as particularly critical for elderly users with limited technological familiarity. While the application successfully improved service efficiency and reduced physical visits to immigration offices, challenges persisted, including limited public awareness and internet connectivity issues in rural areas. The research concludes that human-cantered design principles are essential for inclusive public service technologies and suggests enhancing outreach campaigns through community channels, integrating voice-assisted navigation features, establishing mobile assistance units for first-time users, and developing collaborative partnerships with healthcare providers and disability advocacy groups to further optimize system effectiveness.